HUBUNGAN GANGGUAN TIDUR PADA PEKERJA SHIFT DENGAN KEJADIAN KECELAKAAN KERJA DI TERMINAL PETIKEMAS - Ayu Wanda Saraswati; Indriati Paskarini (Universitas Airlangga, 2018)
Working at night can causes some impacts on shift worker’s life, such as their health, safety and also social life. Sleep disturbance is one of the impacts from working at night, and it will influenced their health and safety, as well as the social life of shift workers. This condition will increased the risk of work accident on night shift. The purpose of this research is to study the relationship between sleep disturbance and work accident at cargo handling terminal. This research is categorized as case-control research, and using primary data that retrieved by giving questionnaires to the shift workers. The result of statistical test which using Chi-Square test shows that there is a relationship between sleep disturbance in shift workers and the work accident at cargo handling terminal (0.0015 <0.005). The relationship value between this two variable is 0.322. The effort that can be done to lower the sleep disturbance is doing a good combination of adequate hours of sleep and proper consumption of caffeine. Keywords: accident, loading and dismantling container port, night work, shift worker, sleep disturbance.